1997
DOI: 10.1021/bk-1997-0666.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Issues in Synthesis-Gas Fermentations

Abstract: Biomass-derived synthesis gas can be readily converted into fuels and chemicals by anaerobic microorganisms. However, synthesis -gas fermentations typically exhibit low volumetric productivities due, in part, to low cell densities, production of unwanted by -products, and slow transfer of the synthesis gas into the liquid phase. Engineering approaches to improve bioreactor productivities are discussed, and recent advances in this area are summarized. Particular emphasis is placed on the use of bioreactor desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
(27 reference statements)
0
29
0
Order By: Relevance
“…[1][2][3][4] Therefore, syngas fermentation is a potential pathway for converting biomass to a variety of fuels and chemicals because of its low cost and potentially high efficiency. The actual conversion efficiency depends on the microorganism and the desired product but can easily be 35% or higher.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore, syngas fermentation is a potential pathway for converting biomass to a variety of fuels and chemicals because of its low cost and potentially high efficiency. The actual conversion efficiency depends on the microorganism and the desired product but can easily be 35% or higher.…”
Section: Introductionmentioning
confidence: 99%
“…Syngas must be transferred from the gas phase to liquid phase so cells can convert it to products. Mass transfer is limited due to low solubility of CO and H 2 in the fermentation medium (Vega et al, 1990;Wilkins and Atiyeh, 2011;Worden et al, 1997).…”
mentioning
confidence: 99%
“…Figure 2 shows the enhancement of CO-water volumetric mass transfer with various electrolytes as a function of electrolyte concentration. As shown in Figure 2a, the CO-water mass-transfer enhancement increased with electrolyte concentration when CuSO 4 2 O, the enhancement first increased, reached a maximum, and then decreased with increasing electrolyte concentration. For the sulfate salts, the maximum enhancement differed from 3.4 to 4.7 depending on the cation type.…”
Section: Methodsmentioning
confidence: 85%
“…Others have suggested that Gibbs elasticity, which is also proportional to (dγ/dc) 2 , provides an explanation for the influence of electrolytes on bubble coalescence. [30][31][32] Christenson and Yaminsky 31 suggested that the elastic response of the interface to changes in film thickness increases the coalescence time in electrolyte solutions compared to pure liquids (the Marangoni effect).…”
Section: Table 1 Mass-transfer Enhancement For Added Electrolytes Anmentioning
confidence: 99%
See 1 more Smart Citation